PENGARUH PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI 3 NEGARA ASEAN (SINGAPURA, INDONESIA, DAN KAMBOJA) - Wayan Dea Maharani Ardiana; Anak Agung Bagus Putu Widanta (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Economic growth serves as a key indicator in determining the level of a country's development. Countries with high economic growth typically demonstrate macroeconomic stability, a conducive investment climate, and sound fiscal management. This study aims to analyze the influence of Foreign Direct Investment (FDI), government expenditure, and inflation on economic growth in three ASEAN countries with different income levels as classified by the World Bank: Singapore (high income), Indonesia (upper-middle income), and Cambodia (lower-middle income). The research employs secondary data obtained from the World Bank covering the period from 1993 to 2023. A total of 360 observations were analyzed using panel data regression analysis. The findings indicate that Foreign Direct Investment, government expenditure, and inflation simultaneously have a significant effect on economic growth in the three countries. However, the partial effects of each variable differ across countries.